Pablo and Birdy - McGhee, Alison, 1960- (Atheneum Books for Young Readers, 2018)
Pablo, nearly ten, has many questions about his origins and how he arrived at Isla as a baby, but finding the answers may mean losing his lifetime companion, Birdy the parrot.